THE INFLUENCE OF ORGANIZED ACTIVENESS ON SELF-CONFIDENCE IN SEMESTER IV AND VI STUDENTS OF THE ISLAMIC RELIGIOUS EDUCATION STUDY PROGRAM AT THE ISLAMIC COLLEGE OF TEBING TINGGI DELI - Jusua Barus; Abdullah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This research uses a quantitative approach, in which symptoms are measured using numbers. The results of this study, from the results of calculations using the IBM SPSS Statistics version 22 for windows it is known that the tcount is 8.577. With α = 5%, dk = 62-2 = 60, a table value of 1,670 is obtained. From these figures it can be seen that tcount (8.577) > ttable (1.670), as well as the significance value of 0.00 <0.05, it can be concluded if the hypothesis is accepted, it means that there is an effect of organizational activity on the confidence of Semester IV and VI Students of the Islamic Religious Education Study Program Tebingtinggi Islamic High School Deli. Based on the Adjusted R Square value of 0.543 or 54.3%, this shows that if the activity activeness variable can explain the confidence variable of 54.3% the remaining 45.7% (100% - 54. 3%) is explained by the variables Other variables not included in this study such as interpersonal communication, campus environment, learning achievement, peers, etc. are not meticulous in this study. From the results of a simple linear regression equation that has the formulation Y = a + bX + ɛ, the equation is Y = 19.032 + 0.855X. Which means that the constant value (a) of the dependent variable (Y), namely the confidence of 19,032, is positive indicating the predicted value of the average confidence variable will continue to rise by 19,032 units even though the activeness variable is zero, and the the regression coefficient value of the active variable is organized (X ) amounted to 0. 855 indicating a positive sign which means that it shows the magnitude of the role of the organized activity variable (X) on self-confidence with the assumption that the organized activity variable (X) is constant. This means that if the activeness factor increases by 1 unit of value, then it is predicted that self-confidence will increase by 0.855 unit of value assuming the variable of activeness is constant.